A novel application of X-ray computed tomography towards the characterization and interpretation of phase formations, mineral parageneses, and internal features in ancient copper slag from Tepe Hissar, Iran - Benjamin Sabatini; Antoine Allanore (PLoS ONE, 2025)
A selection of metallurgical slag artifacts from the Early Bronze Age site of Tepe Hissar, Iran, were characterized using X-ray computed tomography (XCT), X-ray fluorescence (XRF), X-ray diffraction (XRD), and optical and scanning electron microscopy with energy-dispersive spectrometry (SEM-EDS). The CT scans were used to identify regions of interest and internal features for sectioning, including pores, high-density inclusions, and differences in slag density and porosity distribution. The scans revealed internal features and patterns; however, contiguous metal-rich regions and thick surface minerals masked some features and misrepresented others. This study demonstrates how XCT enables the identification and collection of salient diagnostic information from slag artifacts before sectioning, providing a prescience of internal features and a volumetric 3D record of each artifact. After studying the 3D images, the artifacts were precisely sectioned and examined using optical microscopy, SEM-EDS, and XRD, revealing primary pyrometallurgical phases and secondary mineralizations, stratified slag layers, leaching channels, and internal microenvironments. Secondary precipitates and mineral parageneses within these environments are discussed, referencing the archaeological record, soil salinity, and Pourbaix diagrams. An explanation for the presence of speiss in some slag artifacts from Hissar is also detailed.